2003
DOI: 10.1021/jf030121t
|View full text |Cite
|
Sign up to set email alerts
|

An Assay To Estimate Tannins Added to Postmortem Turkey Meat

Abstract: A method for quantification of tannins in wine was adapted to determine tannins added to turkey meat. Standard curves containing varying amounts of GSE [0, 0.5, 1.0, 1.5, 2.0, 2.5, and 5.0%, (w/w)] as a source of tannins were developed. The R(2) value of the mean standard curve was 0.9992. The overall percent recovery of GSE in meat was determined to be 54.78%. Results showed that estimation of GSE in four out of five of the spiked samples was less than or equal to 10%. It is unclear as to why spiked samples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Ellagitannins and gallotannins may also affect the life of foodstuff due to their antioxidant properties and/or antimicrobial activity (Cao, Sofic, & Prior, 1997;Hager, Howard, & Prior, 2010;Haslam, 1989;Koponen, Happonen, Mattila, & Törrönen, 2007;Lau, King, & Waterhouse, 2003;Michel et al, 2011;Zhang, Wang, Lee, Henning, & Heber, 2009). …”
Section: Importance Of Food Htsmentioning
confidence: 99%
“…Ellagitannins and gallotannins may also affect the life of foodstuff due to their antioxidant properties and/or antimicrobial activity (Cao, Sofic, & Prior, 1997;Hager, Howard, & Prior, 2010;Haslam, 1989;Koponen, Happonen, Mattila, & Törrönen, 2007;Lau, King, & Waterhouse, 2003;Michel et al, 2011;Zhang, Wang, Lee, Henning, & Heber, 2009). …”
Section: Importance Of Food Htsmentioning
confidence: 99%
“…Hydrolysable tannins are heterogeneous groups of natural polyphenolic compounds, with high molecular weight, are water-soluble, and widely found in vegetable feedstuffs and can be extracted from the wood of trees [5]. In monogastric animals, HT have positive effects on the stability of the gastrointestinal microflora and potential antioxidant properties [6]. Previous studies showed that tannins possessed antibacterial, antioxidant, antidiarrheal, and anticancerogenic activities in weaned pigs [7].…”
Section: Introductionmentioning
confidence: 99%
“…These stressors result in low feed intake as well as changes in gut morphology and microbiota, which affect productive performance and increase susceptibility to diseases. The multiple functions of tannin polyphenols also have positive effects on gut microbiota (LAU et al, 2003), gut health and animal performance (BRUS et al, 2013), reducing postweaning diarrhoea (LIU et al, 2020), and stress blood metabolites (CAPRARULO et al, 2020), which can revert weaning effects (HUSSAIN et al, 2021), thereby improving animal production and welfare.…”
Section: Introductionmentioning
confidence: 99%